Development of a Competency Assessment Scale for Head Nurses in Community Hospitals - Kanjananat Tongmuangtunyatep (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
Competent head nurses in community hospitals are essential for achieving healthcare quality improvement. This study aimed to develop and to examine the psychometric properties of a Competency Assessment Scale for Head Nurses in Community Hospitals (CASHNCH). The conceptual framework of the scale development is based on the head nurses’ competencies of Thailand Nursing Council and Midwifery (2013), which includes five domains. The 125 items of competencies were generated and verified by six experts with the scale content validity of .94 with 55-item remained. The scale was tested for the reliability with 30 head nurses in community hospitals using multistage sampling method, the Cronbach’s alpha coefficient of this scale was .99. Six hundred and fourteen head nurses in community hospitals were randomly selected for the field-testing to verify construct validity. The item-total correlation ranged from .43 to .82, and the items were of a good discrimination power. The principle component and oblique rotation with oblimin was used for exploratory factor analysis. The final scale is composed of 52 items with five domains 1) leadership 2) healthcare environment management 3) policy implementation and communication 4) management and 5) professional ethics. The scale was tested with the contrasted group, between 64 head nurses and 68 new nurse graduates, and the significant difference was found (p < .001). The CASHNCH demonstrated the acceptable level of reliability, content validity, and construct validity. Therefore it can be used as a competency assessment scale for head nurses in community hospitals in Thailand.